Turner's syndrome - Etem, Ebru; Elyas, Halit (My University, 2007)
Turner's syndrome is the most common chromosomal abnormality in females, affecting 1:2.500 live female births. Today, Turner sendromu or Ullrich-Turner's syndrome (UTS) may be defined as the combination of characteristic physical features. It is a result of absence of an X chromosome or the presence of a structurally abnormal X chromosome. Its most consistent clinical features are short stature and ovarian failure. The objective of this paper is to review the literature on cytogenetic, adults diseases and psychosocial aspects of Turner sendromu. It is becoming increasingly evident that adults with Turner's syndrome are also susceptible to a range of disorders, including osteoporosis, hypothyroidism, renal and gastrointestinal disease. When diagnosis is confirmed by a chromosome analysis, they should be able to serve as a valuable source of support for the patient and her family. All adults with Turner's syndrome should therefore be followed up by a multidisciplinary team to improve life expectancy and reduce morbidity.
Turner sendromu
Keywords: article; chromosome analysis; clinical feature; cytogenetics; disease predisposition; female; follow up; gastrointestinal disease; human; hypothyroidism; kidney disease; life expectancy; morbidity; osteoporosis; ovary insufficiency; patient care; prevalence; psychological aspect; risk reduction; short stature; social aspect; systematic review; Turner syndrome; X chromosome